2018
DOI: 10.1016/j.jtcvs.2017.10.144
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative extracorporeal membrane oxygenation and the possibility of postoperative prolongation improve survival in bilateral lung transplantation

Abstract: Intraoperative ECMO results in superior survival when compared with transplantation without any extracorporeal support. The concept of prophylactic postoperative ECMO prolongation is associated with excellent outcomes in recipients with pulmonary hypertension and in patients with questionable graft function at the end of implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
191
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 197 publications
(197 citation statements)
references
References 39 publications
3
191
0
3
Order By: Relevance
“…The Munich lung group also published their experience with intraoperative ECMO application, they reported a perioperative mortality of 11.1% and a 1-year survival of 81.5% in the ECMO group and 4.5, and 81.8% in the non- ECMO group [9]. The Vienna group summarized their experiences of intraoperative ECMO implementation in bilateral lung transplantation between 2010 and 2016, and reported a 1-year survival rate of 91% in the ECMO group 82% in the non-ECMO group [22]. Ko et al demonstrate the survival rate in single lung transplantation undergoing ECMO was 66.7% [23].…”
Section: Discussionmentioning
confidence: 99%
“…The Munich lung group also published their experience with intraoperative ECMO application, they reported a perioperative mortality of 11.1% and a 1-year survival of 81.5% in the ECMO group and 4.5, and 81.8% in the non- ECMO group [9]. The Vienna group summarized their experiences of intraoperative ECMO implementation in bilateral lung transplantation between 2010 and 2016, and reported a 1-year survival rate of 91% in the ECMO group 82% in the non-ECMO group [22]. Ko et al demonstrate the survival rate in single lung transplantation undergoing ECMO was 66.7% [23].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients had cystic fibrosis as an underlying diagnosis, and 2 (12.5%) patients were transplanted for sarcoidosis, 2 (12.5%) for extrinsic allergic alveolitis, and 1 (6.3%) for scleroderma. In 5 patients, VA-ECMO was prolonged in the postoperative period according to our institutional preventive strategy for primary graft dysfunction (PGD) [14, 15]. Twelve (75%) patients had PGD grade 0 at 72 h, 1 patient had PGD grade 1, and 3 patients had ungradable PGD.…”
Section: Resultsmentioning
confidence: 99%
“…At our center, postoperative ECMO is used to reduce transpulmonary blood flow to prevent volume overflow to the newly implanted lungs in patients with pulmonary hypertension. Despite the increased risk of postoperative bleeding associated with postoperative ECMO, our group has recently shown that intraoperative ECMO support and prophylactic ECMO prolongation into the early postoperative period result in superior outcomes in recipients with pulmonary hypertension or questionable graft function compared to recipients without ECMO support .…”
Section: Discussionmentioning
confidence: 99%
“…All transplants were performed as bilateral sequential transplants, with or without the use of intraoperative ECMO. Our ECMO protocol was reported recently . For intraoperative use, central cannulation was performed using heparin‐coated tubing (Medtronic Carmeda BioActive Surface; Medtronic Inc., Minneapolis, MN, USA).…”
Section: Methodsmentioning
confidence: 99%